Influence of Kenyan Sign Language on Syntactical Patterns of Written E nglish in Primary Schools for the Deaf in Kenya - Ruth Samoei, C.; Peter Oracha, Adoyo; Edward Kochung, J.; Okutoyi, Joel (2020)
Performance of English in KCPE examination by learners who are deaf ha s shown a trend of low scores as compared to their hearing counterpart s in Nakuru Region. For four consecutive years; 2010, 2011, 2012 & 201 3 English mean scores by learners who are deaf in six primary schools in Nakuru region, Kenya were: 29.74, 31.41, 29.58, & 30.27 respectivel y, while in six selected regular primary schools within the same count ies in the respective years, English mean scores were: 48.74, 47.89, 4 7.87& 56.24. A number of studies have looked at effect of language of instruction and age of onset of hearing loss as variables, yet none co nsidered Effect of Kenya Sign Language (KSL) on written English gramma r. The purpose of this study was to analyse the influence of KSL on sy ntactical patterns of written English written English grammar among le arners who are deaf among learners who are deaf in classes five, six a nd seven in Nakuru Region. Objectives of this study were to: determine influence of KSL on syntactical patterns of written English written E nglish grammar among learners who are deaf in classes five, six and se ven. In this study, Language learning was guided by behaviourist theor y by who? Descriptive research design was used. Data collected was use d to describe nature of existing conditions and relationships. The stu dy was carried out in Nakuru Region, Kenya. Target population comprise d 157 learners who are deaf and 21 teachers for English. Saturated sam pling technique was used to select 141 learners and 18 teachers. Data was collected using document analysis guide and questionnaire for teac hers. Reliability of research instruments with a correlation coefficie nt(r) of 0.75 was accepted in a pilot study involving 16 learners and 3 teachers, constituting 10% of research population. Face validity of research instruments was established by experts in Department of Speci al Needs Education of Maseno University. Qualitative data was organise d into categories and reported in verbatim as themes and sub-themes em erged. Results from this study established that: learners had difficul ties in syntax. OSV word order basic for KSL was evident in students’ written English grammar instead of SVO basic word order for English. T his study concluded that KSL had negative impact on syntactical patter ns of written English, written English grammar among learners who are deaf among learners who are deaf in classes five, six and seven in Nak uru Region, Kenya. This study recommended use of bilingual approach as a media of instruction to enhance mastery of English grammar for lear ners who are deaf. Article visualizations: